The graduation party consumer: market, consumption and opportunities in the Mesoregion Campo das Vertentes – MG (Research, Society and Development, 2021)
The university graduation party event market has presented an opportunity for academic studies in the area of ​​administration, with the possibility of analyzing various managerial and theoretical perspectives. This study aimed to study the behavior of consumers in the Campos das Vertentes Mesoregion of Minas Gerais. The three selected cities, Barbacena, Lavras and São João del Rei, have relevant data on the graduation market, being composed of several private and public institutions of higher education, a substantial number of university students, and with five companies that promote graduation parties. Through a structured questionnaire, in an online format and distributed in person, the university students answered socio-demographic questions and explanatory questions about preferences, perceptions, tastes, economic and cultural. Data analysis relied on techniques of descriptive and multivariate statistics. The results showed that university students are young between 18 and 25 years old, single, financially dependent on someone, and who need help from their family to participate in the graduation party. In this sense, the completion of graduation, becomes a goal and dream to be realized by himself, but with the participation of the family. It was also possible to identify that they prefer parties with the greatest possible diversity of food and drinks available and with more accessible investment values. It is concluded that the market presents several opportunities for companies in the sector, highlighting strategic marketing actions that focus on the concept of symbolism and ritual of passage with family participation.